Exploring the wicked problem dilemmas and driving mechanism of green transition: Evidence from the Yellow River Basin, China - Xie, Weiwei; Dong, Yaning; Jin, Tianlin (Frontiers in Earth Science, 2023)
Green transformation of the Yellow River Basin (YRB) plays an important role in China’s economic and social development, and its ecological security. In view of the wicked problem dilemmas of development and emissions reduction in the YRB, this study theoretically and empirically examines the driving forces of its green transformation. A six-sector green endogenous growth model reveals that low-carbon governance and innovation activities are the main drivers of green transformation. Subsequently, a panel econometric model empirically explores how these drivers can solve the challenges of green transformation. The findings are summarized thus: Low-carbon governance and innovative human and physical capital are key elements of green transformation. The investment-driven and innovation-driven periods regression results confirm that these elements particularly drive green transformation in the latter period. The regional heterogeneity result of the development levels show that drivers can promote green transformation in highly developed areas. At the same time, with the inflow of innovative human capital, the promotion of low-carbon governance and innovative human capital to green transformation has increased to a certain extent. Hence, combining the urban development stage and level to avoid a policy of uniformity may be key to green economic transformation in the YRB.